Drying of rice seeds with natural air - Rangel, Marco Antonio Sedrez; Zimmer, Gilberto Jaime; Villela, Francisco Amaral (Pesquisa Agropecuaria Brasileira, 1997)
The objective of this work was to evaluate the effects of stationary drying with natural air (unheated air) upon drying front speed and upon quality and storability of rice seed. It was used 12 prototipes of aerated bins, 5 meters high and 100 kg capacity. Seeds with 22.9% moisture content were dried in an intermittent drier, to moisture contents of 19.7 and 17.8%, and transferred to bins, calibrated to airflow rates of 1, 3 and 5 m3/min/t, and then dried with natural air until reach 13% moisture content. In an intermittent drier (column seed drier), at 70 °C, control seeds were dried to 12.7%. Germination, accelered ageing, field emergence, whole grain yield and moisture content were evaluated each two months, for 180 days. With airflow rates of 1, 3 and 5 m3/min/t, the drying front reached the superior seed layer after 13, 6 and 4 days, respectively, in bins with 17.8% seed moisture content, and after 15, 6 and 4 days, in bins with 19.7% seed moisture content. Results indicated that stationary drying with natural air is feasible for rice seeds which maintain quality during 180 days of storage. Rice seeds dried in stationary drier with natural air show better whole grain yield than the ones dried in intermittent drier. Airflow rate of 1 m3/min/t is sufficient for drying seed layer of about 5 meters high, with 19.7% moisture content.